Isolation of high quality genomic dna from dryobnanalops beccarii dyer tissues rich in camphor - Liew, Kit Siong (Universiti Malaysia Sarawak (UNIMAS), 2007)
The isolation of high-quality intact genomic DNA is obviously difficult in a variety of plant species due to the presence of high levels of polysaccharides, polyphenolics and other secondary metabolites. These contaminants will co-precipitate with DNA during DNA isolation and purification processes, and therefore, resulting in a brownish DNA pellet that is unsuitable for downstream applications. Most plant genomic DNA isolation protocols for various plant tissues have been established; however these protocols are inefficient in yielding high-quality amplifiable genomic DNA especially from camphor containing timber species, Drynobanalops beccarii Dyer. In this project, the total genomic DNA of Drynobanalops beccarii was successfully isolated using a re-optimized CTAB method based on the Murray & Thompson (1980) and Doyle & Doyle (1990). The modifications include: 1) using 1% =-mercaptoethanol and 2% PVP (Mr 40000) in the extraction buffer, 2) sample incubation time, 40 minutes at 65°C; and 3) DNA precipitation at room temperature (25°C). The isolated DNA pellet was in transparent colour and yielded amplifiable genomic DNA for RAPD-PCR.